Design on a Hybrid Drive Feeding Mechanism of High-speed Industrial Sewing Machine - Zheng Ji; Qiu Weiming; Cui Lintao; Ke Xianglin; Yang Shu (Jixie chuandong)
Aiming at the defects of the traditional feeding mechanism, such as complex structure, low adjustment accuracy and poor flexibility, a flexible hybrid drive feeding mechanism is proposed. In this study, the closed vector method is used to analyze the kinematics of the hybrid drive feeding mechanism, and the functional relationship between the tooth trajectory and the rotation angles of the drive motors is derived. The rotation angles of the drive motor are planned by functions, and the influence of each coefficient in the rotation angle functions on the tooth trajectory is analyzed in detail. The optimization strategies of flexible adjustment of tooth trajectory are also proposed for several practical sewing scenarios. What's more, the load on the tooth is analyzed during the feeding process, as well as the dynamic characteristics of the drive motors under the extreme working conditions by establishing the dynamic simulation model of the hybrid drive feeding mechanism. By using high-speed video equipment and graphic recognition analysis software, the tooth trajectory of the hybrid drive feeding mechanism is tracked and calibrated, and the test results are consistent with the theoretical calculation results. The hybrid drive feeding mechanism has the advantages of simple structure, reliable operation and flexible adjustment, which deeply meets the current production needs of less people, automation and intelligence.